Optimizing Organic Waste Processing through Maggot Cultivation as a Circular Economy and Green Economy Solution: Optimalisasi Pengolahan Sampah Organik melalui Budidaya Maggot sebagai Solusi Ekonomi Sirkular dan Green Economy - Alti, Rahmi Mudia; Rifka Agustianti; Alti, Intan Cynara Valentina Putri; Alti, Ike Yuni Wulandari (Universitas Lancang Kuning, 2025)
Organic waste management is a major challenge in urban areas due to its potential to cause environmental pollution. The cultivation of Black Soldier Fly (BSF) larvae, commonly known as maggots, was introduced as an alternative solution because of their ability to convert organic waste into valuable products. This community service program was conducted in RW 25 with the aim of improving residents’ knowledge and skills in maggot cultivation through socialization, training, cage construction, starter kit distribution, and regular mentoring. Evaluation through pre-test and post-test indicated an increase in community understanding from 42% to 64%. Furthermore, residents successfully carried out four harvesting cycles with an average yield of 2–4 kg per cycle, which were either used as animal feed or sold to generate additional income. The program proved effective not only in reducing the burden of organic waste but also in fostering a sustainable, community-based circular economy model.